2009
DOI: 10.1080/14756360802333182
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and inhibition of rat intestinal alkaline phosphatase by high concentrations of calcium. Reversibility of the processes

Abstract: Intestinal alkaline phosphatase (IAP) is an enzyme of the brush border of the enterocyte. The activity of IAP biphasically depends on calcium. Although calcium increases IAP activity, when calcium is higher than 20 mmole/L, IAP activity decreases and the amount of an aggregated form increases. The reversibility of the effect of calcium and the aggregation process are unknown. The isoelectric point of the enzyme was higher in the presence of calcium, but was the same for the enzyme and the aggregated form. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…Moreover, previous studies demonstrated that 1,25(HO) 2 vitamin D increase the expression of IAP and that IAP activity is related to calcium absorption . We have demonstrated that IAP and Ca interaction results in changes on enzyme activity and calcium absorption . However, the relationship among calcium concentration, IAP activity, and calcium absorption demonstrated in this paper is not as a consequence of changes in 1,25(OH) 2 vitamin D, as the experiment were carried out in vitro with isolated intestinal loop and within isolated duodenal cells.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Moreover, previous studies demonstrated that 1,25(HO) 2 vitamin D increase the expression of IAP and that IAP activity is related to calcium absorption . We have demonstrated that IAP and Ca interaction results in changes on enzyme activity and calcium absorption . However, the relationship among calcium concentration, IAP activity, and calcium absorption demonstrated in this paper is not as a consequence of changes in 1,25(OH) 2 vitamin D, as the experiment were carried out in vitro with isolated intestinal loop and within isolated duodenal cells.…”
Section: Discussionmentioning
confidence: 55%
“…Four percent stacking and 5% separating gels were used . Electrical supply was controlled with an EPS 3500 power supply (Pharmacia Biotech, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In those experiments, it has been demonstrated that this enzyme binds Ca and that its molecular mass increases, probably as a consequence of molecular aggregation. With regard to aggregation, the process is reversible when Ca is removed by the addition of ethylene glycol tetraacetic acid (EGTA) (10) . The results of the experiments described in the present study confirm that %Ca decreases as Ca intake increases.…”
Section: Discussionmentioning
confidence: 99%
“…Ca binds to IAP and causes changes in its activity and molecular mass (9) . The effect of Ca appears to be the consequence of Mg replacement and seems to be important in the stability of the dimeric active structure of IAP (10) . As mentioned before, the expression of proteins involved in the mechanism of Ca absorption is regulated by vitamin D (11) , in a process involving protein synthesis (12) .…”
mentioning
confidence: 99%